กลยุทธ์การพัฒนาธุรกิจอสังหาริมทรัพย์เพื่อความยั่งยืนของบริษัทที่จดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย พ.ศ.2564 - แพรววลัย เสนาวุธ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
At present, global businesses, including the real estate development industry, need to operate by taking account of environmental and social as well as governance (ESG) impacts. The SEC and the Stock Exchange of Thailand have required all listed businesses to disclose information on sustainable operations by the year 2022. Therefore, this research aimed to study business practices of taking into account sustainability based on ESG concept.  Data were collected from 56-1 One Report for the year 2021 of 15 real estate development companies listed on the Stock Exchange of Thailand, divided into 3 large companies, 3 medium companies and 9 small companies, including interviews with entrepreneurs from 3 case study companies.  Data were analyzed on comparative sustainability between company sizes and ESG criteria, totaling 21 topics, concepts and operational practices, including the performance and problems, obstacles encountered in the implementation of such sustainability guidelines.The findings revealed the following: 1) Most companies’ major sustainability vision, mission and corporate value included becoming a leading real estate development company for sustainable business development, creating benefits and responsibility for all stakeholders, especially customers and producing goods as well as services in response to lifestyle needs. 2) Business practices that take account of sustainability: The majority of companies reported on social aspect the most because of the companies’ further development from the determination of social operations in the corporate governance process (CSR in Process), especially labor, social, community issues, followed by governance & economy on the issues relevant to the organization, customers and investors as stakeholders  related to investment and financial returns of the companies with minimal environmental reporting on the topics of disclosing environmental information, environmental management and efficient use of resources. 3) Large companies were remarkable for all-round environmental performance while medium-sized companies focused on  supply chain management and business innovation for society and the environment and small companies aimed to operate by taking account of community and social involvement. 4) The strategies for housing project development based on ESG concept of case study companies consisted of 5 aspects, namely (1) technology and innovation strategy to reduce negative impacts for project development of playing an important role throughout the project development phase  and supporting the implementation of the remaining strategies; (2) product quality control strategy; (3) sales promotion strategy of responding to current consumer behavior; (4) product quality inspection strategy and (5) community management system strategy for  residents satisfaction, reflecting the performance in a concrete way.  This was also part of the three case study companies being listed on Thailand Sustainability Investment (THSI). 5) Major obstacles found in the operations to correspond to  ESG concept were the process of adjusting the management of operational data from within the organization as well as supply chain management to become a sustainable housing development business according to international standards.The study results indicated the situation of business operations and housing project development strategies of the companies based on ESG concept, reflecting adaptation, readiness as well as obstacles of the real estate development business in adopting ESG concept into all housing development processes even during the period when the formal sustainability reporting criteria starting in 2022 have not yet been applied.